Resurrection of Dendropemon sintenisii (Loranthaceae): an endemic mistletoe from Puerto Rico - Caraballo-Ortiz, Marcos A.; Carlo, Tomás A. (Phytotaxa, 2013)
On 25 November 1885 German botanist Paul Ernst Emil Sintenis collected a species of mistletoe in a coffee plantation in Aibonito, a municipality located in the central mountain range of Puerto Rico (Sintenis 2856, GOET). Ignatius Urban examined the specimen and name it Dendropemon sintenisii Krug & Urban (Urban 1897: 25) in honor of its collector. After its description D. sintenisii remained unknown in Puerto Rico and, although it was included in all major floristic treatments of the island, the species was a taxonomic ghost known only from the type specimen (Liogier 1985, Liogier & Martorell 2000, Axelrod 2011). No new specimens were labeled with the name in any herbarium since its original description and serious doubts existed among local botanists about its validity. This uncertainty resulted in the provisional placement of D. sintenisii under the synonymy of D. caribaeus Krug & Urban (Urban 1897: 27) in the recent monograph of Dendropemon by Kuijt (2011). This placement was justified because both the vegetative structures and infructescences of D. sintenisii share similarities with D. caribaeus, and the type specimen lacks flowers, which are key to confidently identify Dendropemon species (Kuijt 2011).